Perspectives of health technology assessment in Poland on the example of analysis of surgical technologies for female stress urinary incontinence treatment - Hetnał, Marcin (2005)
The objectives of this analysis are to show perspectives and barriers of heath technology assessment in Poland and to compare selected surgical methods for female stress urinary incontinence treatment. Methods: 1. Comparisons were based on valid RCTs and CCTs found in systematic review. In case of absence of head to head trials comparing TVT, Burch, MMK, AR, indirect comparison was exercised. Cost analyses were performed. 2. Detailed analysis of literature related to development, legal solutions, socio-economical and political outline of the health technology assessment in Poland were performed. Results and conclusions: 1. The efficacy analysis suggests that the highest cured ratio is achieved with TVT (80,7%), followed by Burch (78,5%), MMK (69,8%) and the lowest effectiveness is represented by anterior vaginal repair (51,7%). The significant differences between TVT and Burch in respect to efficacy in stress urinary incontinence treatment were not found. The difference between objective cured ratios of TVT and AR, TVT and MMK and the difference in efficacy between Burch and MMK, Burch and AR as well is statistically significant. Analysis of complications shows that overall complication rate is significantly higher in Burch than TVT. Direct and indirect cost analyses of the TVT and Burch show that lower costs are generated by the use of TVT. 2. Attempts
Keywords: economic analysis; stress urinary incontinence; systematic review; health technology assessment